EXPLORING THE NEXUS OF VERBAL COMMUNICATION AND PUBLIC RELATIONS - Zhang, Dr. Xin (Global Research Journal of Management and Social Sciences (GRJMSS), 2023)
Effective verbal communication skills are essential in modern society for facilitating social activities and interactions. Public relations, as a specialized field of communication and social regulation, plays a crucial role in fostering connections and collaboration among people. Communication and cooperation with the public are fundamental aspects of public relations activities, enabling the comprehensive transmission of vital information and data and fostering trust and understanding. As public relations continues to evolve, it is essential for individuals to gain a comprehensive understanding of the various forms and techniques of verbal communication within the field. This knowledge is critical for preventing communication challenges and ensuring the smooth functioning of public relations efforts.